Student-Athletes’ Perceptions of Men’s Basketball Head Coaches’ Competencies at 15 Selected NCC AA Division II Christian Colleges - Michael B. Phillips; Colby B. Jubenville (Journal of Applied Sports Management, 2009)
The purpose of this study was to measure the perceptions of student-athletes concerning the coaching competency of 15 head men’s basketball coaches at the Division II level in the National Christian Collegiate Athletic Association (NCCAA). The study utilized the 24-item Coaching Competency Scale (CCS) to collect data on 138 student-athletes participating in men’s basketball from 15 NCCAA member institutions and examined four specific categories: character building competency (CBC), game strategy competency (GSC), motivation competency (MC), and technique competency (TC). Multivariate Analyses of Variance (MANOVA), Analyses of Variance (ANOVA), and Analyses of Covariance (ANCOVA) were computed to examine group differences for the 24 coaching competency factors. Results indicate that player-related factors of starter, non-starter, captain, non-team captain, and academic level were not significant predictors of the combination of coaching competency.
Keywords: Student-athlete experience; player perceptions; coaching competencies; coaching evaluation; small college; college basketball; college basketball coaches